Spectral Composition of Light Affects Sensitivity to UV-B and Photoinhibition in Cucumber - Palma, Carolina Falcato Fialho; Castro-Alves, Victor; Morales, Luis Orlando; Rosenqvist, Eva; Ottosen, Carl-Otto; Strid, Åke (Frontiers in Plant Science, 2021)
Ultraviolet B (UV-B, 280 – 315 nm) and ultraviolet A (UV-A, 315-400 nm) radiation comprise small portions of the solar radiation but regulate many aspects of plant development, physiology and metabolism. Until now, how plants respond to UV-B in the presence of different light qualities is poorly understood. This study aimed to assess the effects of a low UV-B dose (0.912± 0.074 kJ m-2 day-1, at a 6 h daily UV exposure) in combination with four light treatments (blue, green, red and broadband white at 210 µmol m-2 s-1 Photosynthetic active radiation [PAR]) on morphological and physiological responses of cucumber (Cucumis sativus cv. ‘Lausanna RZ F1’). We explored the effects of light quality backgrounds on plant morphology, leaf gas exchange, chlorophyll fluorescence, epidermal pigment accumulation, and on acclimation ability to saturating light intensity. Our results showed that supplementary UV-B significantly decreased biomass accumulation in the presence of broad band white, blue and green light, but not under red light. UV-B also reduced the photosynthetic efficiency of CO2 fixation (α) when combined with blue light. These plants, despite showing high accumulation of anthocyanins, were unable to cope with saturating light conditions. No significant effects of UV-B in combination with green light were observed for gas exchange and chlorophyll fluorescence parameters, but supplementary UV-B significantly increased chlorophyll and flavonol contents in the leaf epidermis. Plants grown under red light and UV-B significantly increased maximum photosynthetic rate and dark respiration compared to pure red light. Additionally, red and UV-B treated plants during with saturating light intensity showed an higher quantum yield of photosystem II (PSII), fraction of open PSII centres and electron transport rate and showed no effect on the apparent maximum quantum efficiency of PSII photochemistry (Fv/Fm) or non-photochemical quenching in contrast to solely red-light conditions. These findings provide new insights into how plants respond to UV-B radiation in the presence of different light spectra.